Review of the Fabrication Techniques of Metal Textile Jewelry (Journal of Fiber Bioengineering and Informatics, 2024)
Textile jewellery is a type of jewellery that has a structure or texture similar/identical to textile products.Although the practice of textile jewellery is evident, there is a lack of a comprehensive overview ofthe techniques, methods, and materials involved. The confusion on how to apply different fabricationtechniques creates difficulty in making metal textile jewellery. The review, therefore, summarises,classifies, and compares the types, techniques, materials, and structures used to make metal textilejewellery. The analysis results show that it is essential to understand the effects produced by differentprocesses. Textile jewellery structures with similar styles can be produced by very different processes,which can be easily confused. This paper clarifies the differences between the processes to help designersmore quickly and accurately select the right process for making jewellery.
Keywords: Textile; techniques; jewelry metal; twisting; filigree; casting; openwork; repoussé; chasing; knitting; crochet; weaving; basketry; knotting